HERMENEUTIKA HADIS KEBEBASAN WANITA PERSPEKTIF ABU SYUQQAH - Sa’adah Ritonga (Farabi, 2017)
This paper presents a hermeneutic tradition of a thinker and former Egyptian political activists - Abu Syuqqah- on the liberation of women in the book of Tahrir al Mar`'ah fi 'Ashri al-Risalah. A study of the book is considered important and useful for the development of scientific traditions. Also provide answers to how the hermeneutic aspects in the book. Then the principles of hermeneutics anything contained therein. Abu Syuqqah desire to overcome problems of the people in his day to do the rereading of the hadiths used scholars highly textual. Therefore, he tries to give an understanding of a hadith by looking at the context and contextual text. So get a deeper understanding relevant. The hermeneutical traditions offered by Abu Syuqqah about freedom, women not only look at the text of the hadith alone but he is very attention to aspects outside the text like attention to psychological, social, historical, and educational aspects of women, so it is really understood how the text of the hadith then see the historical context and the contextual meaning of the hadith see the woman at this time.